Analisis Wacana Cerpen “Bersiap Kecewa Bersedih Tanpa Kata-Kata” Karya Putu Wijaya Terhadap Aspek Konteks Situasi Serta Penanda Kohesi Gramatikal Dan Leksikal - Dita Marlina Sari Puspita Arum; Vadila Fitri Nesa (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2023)
The purpose of this research is to find out the grammatical and lexical aspects of the short story “Being Disappointed, Grieving Without Words” by Putu Wijaya. The method used is descriptive method, qualitative in the form of words. The results of the research show the following things. First, the grammatical aspect which consists of references, subtitutions, conjunctions, and ellipsis. Second, the lexical aspect which consist of repetition, synonymy, antonym, and collocation.